A Reappraisal of Lymphadenectomy in Common Gynecological Cancers - Nassir Habib; Graziella Moufawad; Jad Hayek; Francoise Futcher; Vito Chiantera; Ramon Rovira Negre; Rajesh Devassy; Gabriele Centini; Liliana Mereu (IMR Press, 2023)
Objectives: Lymph node dissection (LND) in gynecological malignancies has always been a cornerstone in the diagnosis of metastasis, it is also considered an important prognostic factor, and a reliable guide to management strategies. However, its incidence of complications, namely lymphedema, vascular injuries and other lesions, has led to a reconsideration of its efficacy and a comparison of the role of systematic vs. sentinel lymph node (SLN) dissection. Mechanism: Review of the literature using keywords such as "lymph nodes", "sentinel lymph nodes", "morbidity and mortality", "gynecological cancers", "endometrial cancer", "ovarian cancer", and "cervical cancer". Findings in Brief: In the case of endometrial cancer, several studies have investigated the efficacy of SLN compared with systematic LND. Most of the results demonstrated the efficacy of SLN dissection in endometrial cancer, with the added benefit of lower morbidity. In patients with ovarian cancer, the mainstay of treatment is debulking with optimal cytoreductive surgery. Recent studies have compared systematic lymphadenectomy to non-lymphadenectomy, with an additional advantage in the cases of lymphadenectomy. However, since its publication, the lymphadenectomy in ovarian cancers (LIONS) trial, has revolutionized the standard of care for patients with advanced ovarian cancer and has called into question the increased morbidity and mortality in systematic lymphadenectomy. In cervical cancers, lymph node status is considered to be the most important prognostic factor. In this case, limiting lymphadenectomy to the borders of the inferior mesenteric artery seems promising, and studies are currently being carried out to investigate the feasibility of SLN dissection instead of systematic lymph node dissection. Conclusions: SLN dissection is associated with lower morbidity and mortality, and has been shown to be superior to systematic lymphadenectomy in several studies. However, more research and specific guidelines are needed to better select either one or the other method in the management of gynecological cancers.